Adolescent bystanders' perspectives of aggression in the online versus school environments. (20th March 2016) - Patterson, Lisa J.; Allan, Alfred; Cross, Donna
ABSTRACT: Researchers' understanding of bystanders' perspectives in the cyber‐environment fails to take young people's perceptions into account and remains imperfect. Interventions encouraging adolescents to help targets of cyber‐aggression are therefore typically based upon traditional school‐based aggression research. Twenty‐four in‐depth interviews with Australian 13–16 year‐olds revealed two themes that reflect how young bystanders perceive differences between aggression online and at school. The physical presence theme suggests that young bystanders struggle to determine online intentions in the absence of body language, leading to hesitancy in reactions and furthermore make it easier for them to ignore online transgressions and avoid becoming involved. The authority theme indicates young bystanders perceive that, compared to the school environment, the online environment lacks clearly established rules, authority figures and formal reporting mechanisms. These differences indicate that unique strategies should be developed to encourage young bystanders to intervene in cyber‐aggression situations.